2006
DOI: 10.2351/1.2355529
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sensation threshold for 3.8 μm radiation from a short duration pulsed laser on the calves of human subjects: A pilot study

Abstract: Articles you may be interested inVisible lesion threshold dependence on retinal spot size for femtosecond laser pulsesThe objective of this study was to determine the threshold for sensing a 3.8 m laser on the skin. The identification of the skin sensation threshold for invisible lasers is useful in providing scientific guidance to the safety community regarding accidental skin exposures. Knowledge of the level of sensation of lasers might be used to show that sensation may not coincide with the exposure limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Due to a lack of data, ANSI recommends that the infrared MPEs for the skin be set at the same level as for the cornea. Recent research [2] [3] indicates that this may be too restrictive, and has suggested a revision of the standards.…”
Section: Introductionmentioning
confidence: 97%
“…Due to a lack of data, ANSI recommends that the infrared MPEs for the skin be set at the same level as for the cornea. Recent research [2] [3] indicates that this may be too restrictive, and has suggested a revision of the standards.…”
Section: Introductionmentioning
confidence: 97%